Cancer-specific epigenetic alterations as investigated from a pharmaceutical perspective - Paul, Thomas (Henry Stewart Talks, 2021)
Chromatin dysregulation in cancer, Features of epigenetic information in cells, Mutated chromatin regulatory factors as tumor drivers, Therapeutic rationale for the use of epigenetic drugs in oncology, First generation epigenetic drugs: DNMT and HDAC inhibitors, Novel therapeutic discoveries in oncology, Biomarkers for patient selection